Respon pertumbuhan cendawan patogenik Fusarium oxysporum terhadap metabolit sekunder cendawan antagonis Trichoderma sp. - Tunjung Pamekas (PendIPA Journal of Science Education, 2020)
AbstraCT[Growth responses of pathogenic fungus Fusarium oxysporum to secondary metabolites of antagonistic fungi Trichoderma sp.] Fusarium oxysporum is a pathogenic fungus that attack various horticultural crops. Disease control using chemical pesticides have caused many negative effects to natural enemies, environment, famers, and consumers.  It is needed to explore other alternative control methods.  Application of secondary metabolite of Trichoderma sp. is a high potential  control method to be used to control  the disease.  The aim of the research was to evaluate the best concentration of secondary metabolites on controlling F. oxysporum in vitro. The research was conducted on August to November  2017 at Plant Protection Laboratory, Faculty of Agriculture, University of Bengkulu.  The research was arranged on CRD with six concentrations of secondary metabolites, namely  0, 10, 25, 50, 75, and 100 ppm with five replications. The research steps were isolation of F. oxysporum and Trichoderma sp., production of secondary metabolites, in vitro test of secondary metabolites to F. oxysporum, and analyse infra red photometer of secondary metabolites.  Variables that were observed were colony diameter 1 – 7 days, length and width of conidia,  density of conidia, and  length and width of germ tubes.   The result showed that application of secondary metabolite gave significantly effect to all variables, except the germ tube width.  The diameter colony of F. oxysporum was inhibited 27.99 – 35.43%, the length and width of conidia were inhibited 49.63% and 49.06%, the density of conidia was inhibited 75%, and the length of germ tube was inhibited 62.47%.  The higher concentration of secondary metabolites the bigger  the growth inhibition of  F. oxysporum. Keywords: Fusarium oxysporum, secondary metabolites, Trichoderma sp., in vitro, infra red photometer